A review on global wind energy policy - Saidur, Rahman; Islam, M.R.; Rahim, N.A.; Solangi, K.H. (Elsevier, 2010)
With the increasing negative effects of fossil fuel combustion on the environment in addition to limited stock of fossil fuel have forced many countries to inquire into and change to environmentally friendly alternatives that are renewable to sustain the increasing energy demand. Energy policy plays a vital role to mitigate the impacts of global warming and crisis of energy availability. This paper explores the wind energy industry from the point of view of the wind energy policy. It is noticed that energy policy could help increasing wind power generation as well as stimulating the energy industry. It may be stated that without specific energy policy, a country would not be able to solve the acute problems like reducing greenhouse gases (GHGs) emission, scarcity of energy, etc. This paper discussed the existing successful energy policies for few selected countries. Based on literatures, it has been found that FIT, RPS, incentives, pricing law and Quota system are the most useful energy policies practiced by many countries around the world. Then, status of wind energy policy for Malaysia was investigated and compared with few selected countries around the world.